Digital Marketing Communication to Improve Marketing of Candle Products from Waste Management in an Effort to Empower Communities in Kembangan, West Jakarta - Briandana, Rizki; Andika, Julpri; Z, Annisa Hakim (Universitas Mercu Buana, 2025)
The issue of used cooking oil waste is currently not as much of a concern as the issue of plastic waste because many people take it for granted. Based on discussions with the Head of RT.15 RW.06 North Kembangan Village, West Jakarta, and also field observations, 220 families in the area have difficulty managing waste from used cooking oil. To overcome this, various efforts were made so that the community had an understanding of the impact of using or disposing of used cooking oil. In addition, the waste of used cooking oil generated has the potential to increase economic empowerment and improve skills in utilizing the waste into candles. The purpose of this activity is to market the candle products produced through digital marketing communication with several stages of the method by conducting socialization and training for the community about the dangers of used cooking oil waste and ways to recycle and manage used cooking oil waste in an environmentally friendly manner. Then apply the technology of filtering used cooking oil so that the community does not wait for the oil to settle too long and create an account on e-commerce as a marketing tool for products made from used cooking oil. The results of this activity show that participants can understand the material provided, and it is hoped that participants can implement waste management from used cooking oil.